Determinants of mortality after massive transfusion - A prospective study - Divya Venugopal; Susheela Jacob Innah; Aboobacker Mohamed Rafi; Ramesh Bhaskaran (Asian Journal of Transfusion Science)
INTRODUCTION: Massive hemorrhage calls for massive transfusions (MTs) to maintain adequate hemostasis. Massive transfusion protocols (MTPs) are the appropriate treatment strategy for such patients replacing conventional use of crystalloids. These help in standardizing and optimizing the delivery of blood components in a well-balanced ratio. AIM AND OBJECTIVES: The aim of the study is to propose an ideal ratio of blood components for MTP after assessing relationship between ratios of blood components transfused and mortality. METHODOLOGY: MT was defined as receiving >4 packed red blood cell (PRBC) units within 1 h with the anticipation of continued need for blood products. All MT patients above 13 years of age regardless of cause of bleed were included in the study from December 2015 to October 2017 accounting for a total of 61 patients. Subgroup categorization of study population was done, and physician-driven ratios of the blood components were calculated for each case. The ratios were grouped as high (>1), equal (=1), and low (<1) ratios of fresh frozen plasma (FFP):PRBC and platelet: PRBC, and the relationship of these ratios to the clinical outcome in terms of mortality was examined. RESULTS AND DISCUSSION: Sixty-one patients underwent MT of which the overall hospital mortality rate was 8.1% with 100% mortality among patients with penetrating trauma followed by 25% with gastrointestinal bleed. Emergency admission was an independent risk factor for mortality. Hypotension before the initiation of MT was detrimental for survival. Efficient communication existed between the treating physicians and transfusion. Majority of survivors received equal ratios of FFP: PRBC and platelet: PRBC, and all nonsurvivors received low ratios of FFP: PRBC. Analysis was statistically indicating better survival with 1:1:1 ratio of PRBC: FFP: platelet. CONCLUSION: The need of the hour is to establish an institutional MTP and ensure compliance with the same. A prospective randomized controlled trial needs to be done to overcome the limitations and confounders of the present study and establish a universal protocol.